Provisions of Public Housing Savings Policy Based on Public Welfare According to Sharia Economic Law - Saifuddin, Muhammad Azhar; Yasin, Achmad (Department of Islamic Economic Law, Faculty of Sharia, Sultanah Nahrasiyah State Islamic University, Lhokseumawe, 2024)
Abstract: This study was conducted to measure the extent of the implementation of the People's Housing Savings (Tapera) policy by referring to Law No. 4 of 2016 and PP Tapera No. 25 of 2020 which will be combined using the principles of Sharia Economic Law. This program is an alternative solution to provide access to ownership of livable housing; with affordable housing prices for low and middle income groups. This study focuses on the suitability of the Tapera Program with the principles of Sharia Economic Law in terms of welfare. The research method used is an empirical-qualitative method with a case approach with a study of literature available from various financing platforms. The results show that Tapera is a solution to improve people's welfare by providing fulfillment of basic community needs, and easy financing using sharia principles. This study provides recommendations on adjusting the contract to support an effective program of the Tapera policy from the aspect of reporting and supervision that is more structured, transparent and accountable in order to fulfill public trust.